Research on the Oil Cooling Structure Design Method of Permanent Magnet Synchronous Motors for Electric Vehicles - Shijun Chen; Cheng Miao; Xinyu Chen; Wei Qian; Songchao Chu (Energies)
Permanent magnet synchronous motors for electric vehicles (EVs) prioritize high power density and lightweight design, leading to elevated thermal flux density. Consequently, cooling methods and heat conduction in stator windings become critical. This paper proposes a compound cooling structure combining direct oil spray cooling on stator windings and housing oil channel cooling (referred to as the winding–housing composite oil cooling system) for permanent synchronous motors in EVs. A systematic design methodology for oil jet nozzles and housing oil channels is investigated, determining the average convective heat transfer coefficient on end-winding surfaces and the heat dissipation factor of the oil channels. Finite element analysis (FEA) was employed to simulate the thermal field of a 48-slot 8-pole oil-cooled motor, with further analysis on the effects of oil temperature and flow rate on motor temperature. Based on these findings, an optimized oil-cooled structure is proposed, demonstrating enhanced thermal management efficiency. The results provide valuable references for the design of cooling systems in oil-cooled motors for EV applications.